DESAIN INSTRUMEN TES THREE TIER MULTIPLE CHOICE UNTUK ANALISIS PEMAHAMAN KONSEP PESERTA DIDIK (Universitas Negeri Semarang, 2019)
A learning disability identification students in understanding the concept of chemical need a right required test. But, a few teachers has not carried out the analysis on understanding the concept of students because as yet there are an instrument used for analysis. One way of determining the understanding the concept of school tuition is using a diagnostic test. This research is developing three tier multiple choice diagnostic intrument to analyze the conceptual understanding of 10th grade students in oxidation-reduction reactions concepts and chemical nomenclature. This study was kind of research and development study. The model of development used is four D model by S. Thigarajan, Dorothy S. Semmel and Melvyn I. Semmel. Research subjects is 10th grade science students of Semarang Islamic Senior High School. Instrument that used is three tier multiple choice diagnostic test instrument consisting of 23 item questions. Every item question has five alternative answers in tier one, five alternative reasons in tier two, and sure whether or not to answer in tier three. Research result shown that the developed instrument was good and valid with instrument reliability value was 0,90 and instrument validity value was 92%. Data result was analized descriptively and quanitatively. Result of students conceptual understanding shows that 53.56% of students understand the concept, 44,15% of students are misconception, 0,60% of students are chancy, 0,97% of students less understand the concept, 0,72% of students do not understand the concept.